Electrodeposition of Cu2O nanostructures with improved semiconductor properties. Issue 1 (1st January 2021) - Boulett, Andrés; Pizarro, Guadalupe Del C.; Martin-Trasanco, Rudy; Sánchez, Julio; Tasca, Federico; Linarez Pérez, Omar E.; Tello, Alejandra; Oyarzún, Diego P.
Abstract: In the present research, nanocomposites based on copper (I) oxide poly(1-vinyl-2—pyrolidone-co-itaconic acid) nanostructures (Cu2 O/p(NVP-co-AI)) were synthesized by the electrodeposition method using the copolymer p(NVP-co-AI) as a stabilizing agent in the reduction of Cu +2 to Cu + . The chemical and physical properties of the nanostructures were characterized by techniques such as scanning electron microscopy, infrared (IR) spectroscopy, Raman and ultraviolet-visible spectrophotometry. The obtained nanostructures are mainly a mixture of agglomerated nanospheres with a diameter of approximately 78 to 91 nm, with an alternation of nanolaminar structures, composed of copper (I) oxide species. In the case of the Cu2 O/p(NVP-co-AI) nanocomposite, it was observed a decrease in the carbon-oxygen vibration links of the carbonyl groups in IR intensity for the polymer when it was dissolved in the electrolytic solution, which indicates that interactions are produced by the carbonyl groups with the Cu2 O species. In addition, bandgap values of 1.80 and 1.63 eV were estimated by the Kubelka–Munk method for Cu2 O and Cu2 O/p(NVP-co-AI) samples, respectively.